Metabolomic and transcriptomic exploration of the uric acid-reducing flavonoids biosynthetic pathways in the fruit of Actinidia arguta Sieb. Zucc. - Wang, Yubo; Zhang, Minghui; Dong, Kuiling; Yin, Xiaojuan; Hao, Chunhui; Zhang, Wenge; Irfan, Muhammad; Chen, Lijing; Wang, Yong (Frontiers in Plant Science, 2022)
Flavonoids from Actinidia arguta Sieb. Zucc. can reduce uric acid in mice. However, the molecular basis of its biosynthesis is still unclear.In this paper, we used a combination of extensive targeted metabolomics and transcriptomics analysis to determine the types and differences of flavonoids in the fruit ripening period (August to September) of two main cultivated varieties in northern China.The ethanol extract was prepared, and the potential flavonoids of Chrysin (Flavone1), Rutin (Flavone2) and Daidzein (Flavone3) in Actinidia arguta Sieb. Zucc. were separated and purified by HPD600 macroporous adsorption resin and preparative liquid chromatography.The structure was identified by MS-HPLC, and the serum uric acid index of male Kunming mice was determined by animal model test.125 flavonoids and 50 differentially regulated genes were identified. The contents of UA (uric acid), BUN (urea nitrogen), Cr (creatinine), GAPDH in mouse serum and mouse liver glycogen decreased or increased in varying degrees.This paper reveals the biosynthetic pathway of uric acid reducing flavonoids in the fruit of Actinidia arguta Sieb. Zucc., a major cultivar in northern China, and provides valuable information for the development of food and drug homologous functional foods.